El caso de Yoandy Leal: un análisis del proceso de naturalización en el voleibol brasileño - Ribeiro, Carlos Henrique de Vasconcellos; Garcia, Rafael Marques; Nascimento, Diego Ramos do; Rojo, Jeferson Roberto; Almeida , Larsson Alves de; Pereira, Erik Giuseppe Barbosa (Lecturas: Educación Física y Deportes, 2020)
The aim of this research is to problematize the naturalization process of the Leal player in Brazilian volleyball. Studying this player is to understand a little more about how entities that run sports, confederations at the global level, and federations at the local level, act to legitimize and protect the issue of nationality changes, creating regulations for the eligibility and restrictions of athletes in their sports. We adopted two methodological instruments to obtain our results. The first instrument was news analysis, the second was the application form for changing the federation, instituted by the International Volleyball Federation in the “Sport Regulations”. From the point of view of the labor market, the technical specificities achieved by years of dedication, and the free movement to sign contracts with different companies, we infer that the restrictions do not make sense. Therefore, they are concentrated on athletes who have already reached a high technical level and are at the most productive chronological age. For those who did not participate in national teams or reached the age of 35 for men and 32 for women, there is flexibility in the eligibility conditions.